Some Preliminary Findings from a Laboratory Experiment on the Usefulness of Financial Accounting Information to Security Analysts - Pankoff, Lyn D.; Virgil, Robert L. (Journal of Accounting Research, 1970)
Lyn D. Pankoff, Robert L. Virgil, Some Preliminary Findings from a Laboratory Experiment on the Usefulness of Financial Accounting Information to Security Analysts, Journal of Accounting Research, Vol. 8, Empirical Research in Accounting: Selected Studies 1970 (1970), pp. 1-48